PENENTUAN KUALITAS DAN KOMPOSISI MINYAK HASIL EKSTRAKSI DARI BIJI BUNGA MATAHARI YANG TUMBUH DI DAERAH PANCURBATU KABUPATEN DELISERDANG - Mariana Br. Surbakti (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractA  research of determinining the quality oil that extracted from local sun flower  seeds oil measuring of water concentration, peroxide value, free fatty acid (FFA) and also fatty acids compotition by gas chromatography was carried out. Based on research result, the highest oil concentration on extraction oil of sun flower seeds oil  32,45%.  Based on result analysis of water concentration, peroxide value and FFA from sun flower seeds oil were produced by company which water concentration (0,133%), peroxide value (1,983meq/kg) and FFA(0,079%). Result analysis from oil that extracted local sun flower seeds oil which water concentration (0,44%), peroxide value (5,22meq/kg) and FFA(0,47%). Based on analysis of gas chromatography, the are 13 kinds of identified fatty acidsf rom oil were produced by company and analysis of gas chromatography, there are 12 kinds of  identified fatty acids in extraction oil from local sun flowers seed.Keywords:Quality, composition, extraction, sun flower seed, pancurbatu